Peran Komunikasi Guru Ngaji Dalam Menumbuhkan Minat Belajar Iqra Pada Anak Usia Dini - Irpah Ramadani Munte; Ruwaidah; Fitri Endang Srimulat (Kartika: Jurnal Studi Keislaman, 2026)
This study examines the role of communication between Quran teachers in fostering interest in learning Iqra in early childhood at the Amaliyah Mosque in Lobu Rampah Village, North Labuhanbatu Regency. This study uses a qualitative phenomenological approach with a descriptive-interpretive design. Data were collected through triangulation that includes participant observation, in-depth semi-structured interviews, and documentation studies. The research subjects included Quran teachers as primary informants and early childhood, parents, and mosque administrators as supporting informants. Data analysis used the interactive model of Miles, Huberman, and Saldaña through the stages of data reduction, data presentation, and verification of conclusions. The results of the study revealed three main findings. First, Quran teachers apply a combination of verbal and nonverbal communication in an integrated manner, including the use of simple language, variations in intonation, repetition methods, affective expressions, and continuous positive reinforcement. Second, empathetic and supportive communication has been shown to stimulate and sustain children's interest in learning through enjoyable and spiritually meaningful learning experiences. Third, communication effectiveness is simultaneously influenced by three factors: the teacher's communicative competence, the child's psychological characteristics, and the learning environment